Effects of Boko Haram Violence on Western Schools System in Yobe State of Nigeria - Dachia, Alhaji Duna; Kyauta, Amadu Muktar A. (NIU Journal of Humanities, 2018)
The study is aimed at assessing the effects of Boko Haram Violence on Western schoolsSystem in Yobe State, Nigeria. One objective was formulated to guide the study, specifically to establish how Boko Haram violence has affected western schools system in Yobe State. A descriptive research  design was adopted in which the instruments for data collection was a 10 items questionnaire based on 4-point Likertâ€™s scale of staff ofYobe State universal Basic education Board, teachers, head of schools and PTA/Community members were conducted as a means of generating primary data. The data collected was analyzed using the descriptive statistics of mean and standard deviation analysis through a statistical package for social sciences (SPSS 16.0 Version) using frequency tables and percentage. The study findings among other revelations discovered that Boko Haram has attacked schools resulting in the indiscriminate destruction of schools infrastructure and the teaching and learning materials, loss of teachers, killing and kidnapping of school children as well as recruiting children of school going age as suicide bombers and spies. This therefore, has negatively affected the quality and standards of western schools system in Yobe State. The study recommended that the federal government should ensure educational facilities are adequately secured, especially in the northern States to forestall attacks on the school which claim the lives of pupils and their teachers alike, while also leading to wanton destruction of schools infrastructure. Equally, the schools being destroyed by the Boko Haram should be rebuilt and children should be encouraged to go back to schools. Teachers, particularly in Yobe State and northern part of the country should be motivated by special allowances to amelioratethem from untold hardship they suffer as a result of Boko Haram violence. This ensure a high rate of retention of teachers in the school system.On schools internal security system daily school attendance record books should be adopted by the all schools in Yobe State, likewise studentsâ€™ movement record book should be introduced and kept by teachers with a daily report to the school head.This will make the school authorities to understand and have controls of the school internal security system during the school hours for the betterments of the students, teachers/personnel within the school environment and society at large. Keywords : Boko Haram, Violence, and Western Schools System.